Predicting In‐Hospital Mortality in COVID‐19 Older Patients with Specifically Developed Scores. Issue 1 (30th November 2020) - Covino, Marcello; De Matteis, Giuseppe; Burzo, Maria Livia; Russo, Andrea; Forte, Evelina; Carnicelli, Annamaria; Piccioni, Andrea; Simeoni, Benedetta; Gasbarrini, Antonio; Franceschi, Francesco; Sandroni, Claudio; ,
Abstract : Background/Objectives: Several scoring systems have been specifically developed for risk stratification in COVID‐19 patients. Design: We compared, in a cohort of confirmed COVID‐19 older patients, three specifically developed scores with a previously established early warning score. Main endpoint was all causes in‐hospital death. Setting: This is a single‐center, retrospective observational study, conducted in the Emergency Department (ED) of an urban teaching hospital, referral center for COVID‐19. Participants: We reviewed the clinical records of the confirmed COVID‐19 patients aged 60 years or more consecutively admitted to our ED over a 6‐week period (March 1st to April 15th, 2020). A total of 210 patients, aged between 60 and 98 years were included in the study cohort. Measurements: International Severe Acute Respiratory Infection Consortium Clinical Characterization Protocol‐Coronavirus Clinical Characterization Consortium (ISARIC‐4C) score, COVID‐GRAM Critical Illness Risk Score (COVID‐GRAM), quick COVID‐19 Severity Index (qCSI), National Early Warning Score (NEWS). Results: Median age was 74 (67–82) and 133 (63.3%) were males. Globally, 42 patients (20.0%) deceased. All the score evaluated showed a fairly good predictive value with respect to in‐hospital death. The ISARIC‐4C score had the highest area under ROC curve (AUROC) 0.799 (0.738–0.851), followed by the COVID‐GRAM 0.785 (0.723–0.838), NEWS 0.764 (0.700–0.819), and qCSI 0.749 (0.685–0.806). However, these differences were not statistical significant. Conclusion: Among the evaluated scores, the ISARIC‐4C and the COVID‐GRAM, calculated at ED admission, had the best performance, although the qCSI had similar efficacy by evaluating only three items. However, the NEWS, already widely validated in clinical practice, had a similar performance and could be appropriate for older patients with COVID‐19.